Overview Of Nurses' Knowledge About Progressive Mobilization In The Intensive Care Unit (Icu), Surgery, Internal Disease Prof. Dr. H.M Chatib Quzwain Sarolangun - Nurlaili Andraini; Oktarina, Yosi; Subandi, Andi (Program Studi Keperawatan Universitas Jambi, 2024)
Bed rest is a risk factor for infection, contractures, pressure ulcers, and blood clots. Stating that after 2 weeks of bed rest, there can be a loss of muscle mass of 5%-9%and a decrease in muscle strength of up to 20%-27% To describe the knowledge of nurses about progressive mobilization in the intensive care unit (ICU), surgery, internal medicine, Prof. Dr. H. M. Chatib Quzwain Sarolangun. This study uses a quantitative descriptive study plan, namely a research design in which measurements or observations are carried out simultaneously at one time to find out the Description of Nurses' Knowledge About Progressive Mobilization in the Intensive Care Unit (ICU), Surgery, Internal Medicine, Prof. . Dr. H.M Chatib Quzwain Sarolangun. The distribution of the age frequency of the 51 respondents with the highest knowledge was 32 respondents (62.7%). So it can be concluded that the respondents in this study had more high knowledge than those with low knowledge It is known that from51respondents the most are high knowledge as many as 32 respondents (62.7%). So it can be concluded that the respondents in this study had more high knowledge than those with low knowledge. The results of this study are expected to be used as input, theory and reference material, especially for nurses about progressive mobilization in critically ill patients in the ICU, Surgery and Internal Medicine.